Factors contributing to physical activity among university employees in East Malaysia : a cross-sectional study - Yassimear AU; Cheah, Whye Lian; Myat SB; ViviaN AS; Edward Mc’carter JOK AAT; Sai Dharshyini M; Amira R (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Physical activity (PA) is known to have numerous health benefits. However, despite the frequent emphasis on the importance and benefits of being physically active, the number of people engaged in regular physical activity is still on the low side. This study aims to identify the factors that can influence physical activity levels among staffs from a public university staff in Sarawak, Malaysia. This was a cross-sectional study using a self-administered questionnaire distributed online. A total of 163 of Universiti Malaysia Sarawak (UNIMAS) staffs comprising of 37.4% academician and 62.2% non-academician participated in this study. The participants were selected using a multistage sampling method. Multiple logistic regression (MLR) was performed to examine the factors associated with physical activity level. Majority of the respondents were female (74.2%), Malays (60.1%), married (65.5%), non-academic staffs (62.6%), had tertiary education (85.9%) with mean working hours per day of 8.25 hours. Physical activity (PA) level measured by International Physical Activity Questionnaire (IPAQ) showed the majority of respondents had a moderate PA level (56.4%), followed by a high PA level (33.7%) and a low PA level (9.8%). There were significant findings on the association between exercise attitude barrier (p=0.003) and self-efficacy (p=0.009) with physical activity level. Multiple Logistic Regression analysis showed that exercise attitude barrier (OR=1.170, 95% CI=1.027, 1.334, p=0.019) and self-efficacy (OR= 1.091, 95% CI= 1.015, 1.172, p=0.017) was associated with low and moderate PA level. The findings indicated that exercise attitude barrier and self-efficacy influence the outcome of physical activity level among the respondents.